The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1810-522x-53-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of the sea urchins Temnopleurus toreumaticus Leske, 1778 and Temnopleurus reevesii Gray, 1855 (Camarodonta: Temnopleuridae)

Abstract: Background: Sea urchin larvae near metamorphosis form an adult rudiment that is a complex of the juvenile structures. However, the details of the mechanisms that form the adult rudiment are unknown. The temnopleurid sea urchins Temnopleurus toreumaticus and Temnopleurus reevesii occur in Japan, but the development of their juvenile morphology has not been described. In this study, we observed their development by light and scanning electron microscopy to follow the adult rudiment formation and to consider the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

6
1

Authors

Journals

citations
Cited by 12 publications
(43 citation statements)
references
References 22 publications
7
36
0
Order By: Relevance
“…The final degree of invagination is about 94% (Fig. 5B) and the primary pore canals of this species do not maintain the body width (Kitazawa et al, 2014). We suggest that the continuous invagination occurs by elongation of the archenteron itself.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The final degree of invagination is about 94% (Fig. 5B) and the primary pore canals of this species do not maintain the body width (Kitazawa et al, 2014). We suggest that the continuous invagination occurs by elongation of the archenteron itself.…”
Section: Discussionmentioning
confidence: 93%
“…These results indicate that the feature at the tip of the archenteron may cause species-specific invagination or the formational process of the coelomic pouches. This conclusion is supported by findings that the pattern of formation of the primary pore canal from the coelomic pouches is different among these species (Kitazawa et al ., 2012, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, however, we reported that adult rudiment formation in larvae of Mespilia globulus, Temnopleurus toreumaticus, and T. reevesii depends on a cell mass (CM) instead of the amniotic cavity (Kitazawa et al, 2012(Kitazawa et al, , 2014, as likewise identified in T. hardwickii (Fukushi, 1959) and Genocidaris maculata (Ubisch, 1959). Recently, however, we reported that adult rudiment formation in larvae of Mespilia globulus, Temnopleurus toreumaticus, and T. reevesii depends on a cell mass (CM) instead of the amniotic cavity (Kitazawa et al, 2012(Kitazawa et al, , 2014, as likewise identified in T. hardwickii (Fukushi, 1959) and Genocidaris maculata (Ubisch, 1959).…”
Section: Introductionmentioning
confidence: 90%
“…Morphologically, a primary pore canal (PPC) forms and elongates from the left coelomic pouch to the dorsal ectoderm, and then becomes a duct-like structure connecting the juvenile water vascular system to a madrepore (Kitazawa, Kobayashi, Kasahara, Takuwa, & Yamanaka, 2012;MacBride, 1914;Okazaki, 1975); some species form two PPCs initially, but thereafter the right PPC degenerates (Hara, Kuraishi, Uemura, & Katow, 2003;Kitazawa et al, 2012Kitazawa et al, , 2014. Morphologically, a primary pore canal (PPC) forms and elongates from the left coelomic pouch to the dorsal ectoderm, and then becomes a duct-like structure connecting the juvenile water vascular system to a madrepore (Kitazawa, Kobayashi, Kasahara, Takuwa, & Yamanaka, 2012;MacBride, 1914;Okazaki, 1975); some species form two PPCs initially, but thereafter the right PPC degenerates (Hara, Kuraishi, Uemura, & Katow, 2003;Kitazawa et al, 2012Kitazawa et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%